Dampak Risiko Kredit, Suku Bunga dan Likuiditas terhadap Profitabilitas Bank - Sinta Purnama Sari; Suhendro Suhendro; Riana Rachmawati Dewi (Universitas Batanghari Jambi, 2021)
This study aims to determine the effect of the variable Credit Risk, Interest Rates, Liquidity on Profitability simultaneously or partially to influence the banking subsector companies listed on the IDX for the 2016-2019 period. The data source is secondary data. The method used in this research is the classical assumption test and multiple linear regression analysis with the help of the SPSS version 21 program. There are 42 populations of banking subsector companies listed on the IDX for the 2016-2019 period. The sample was selected from a purposive sampling method of 13 companies from several criteria. The results of this study indicate that credit risk affects bank profitability. Meanwhile, interest rates and liquidity do not affect bank profitability.